Curso a distância de análise do comportamento para professores em formação - Lorena, Angela Bernardo de (Universidade Federal de São Carlos, 2015)
The contribution of Behavior Analysis is useful for teachers, primarily the studies about principles of behavior. The goal of this doctoral was to describe the construction and implementation of an extension course for teachers in training from a context not yet explored in national literature: Distance Education. Article 1 presents the process of construction of an extension course designed to teach some principles of behavior - reinforcement, punishment and extinction -, having as target audience student teachers of the undergraduate degree in Pedagogy of the Open University System of Brazil. The activities proposed for the extension course were drawn from the preliminary identification of behavioral-objectives. There were ten tasks and five teaching conditions. Some aspects of the data are discussed, such as the number of registered participants and evasion. Article 2 aims to evaluate the teaching of the concepts of reinforcement, punishment and extinction for six participants from Article 1, considering three activities and two teaching conditions of the extension course. In order to analyze the data, we have considered the rate of occurrence of three thematic groups: 1) To identify or describe the concept of reinforcement; 2) To identify or describe the concept of punishment; 3) To identify or describe the procedure of extinction. The results showed that the learning conditions were sufficient to teach reinforcement for all participants. However, the concepts of punishment and extinction reached only part of the participants, indicating a need to revise the conditions of teaching. This thesis contains, in addition to the two articles, a section for discussion of the data of eleven participants approved in the extension course. This work opens a new research front, approaching the technologies of teaching developed by behavior analysts in Distance Education and its contributions to the field of Education.
Keywords: Psicologia educacional; Analise do comportamento; Educação a distância; Professores - formação; Tecnologia de ensino; Behavior Analysis; Distance Education; Teacher Training; Technology of Teaching; Education; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM